Brettanomyces anomalus, a double drawback for cider aroma. (March 2019) - Guichard, Hugues; Poupard, Pascal; Legoahec, Laurie; Millet, Mélanie; Bauduin, Rémi; Le Quéré, Jean-Michel
Abstract: Sixty-six French ciders were collected and characterized to build up a data base of eighty-eight variables, including sensory descriptors, aroma description and physicochemical variables. A classification in four main sensory categories was made on the basis of sensorial data.Fruity-Floral ciders were rich in acetate esters and low in volatile phenols, in opposition withphenol-like oroff-flavour ciders having an inverse ratio. In order to explain this observation, an essential result was the demonstration of Brettanomyces anomalus implication, not only in volatile phenol synthesis, but also in acetate ester degradation. Brettanomyces anomalus exhibited an intracellular acetyl esterase activity. At last, both mechanisms, acetate ester degradation and phenol synthesis, contribute to the decrease of cider fruitiness. Highlights: Comparison on characteristics of fruity and defect ciders are presented. Segmentation in four sensory classes with specific aroma composition is shown. Brettanomyces contamination impact on fruitiness is presented. Brettanomyces is involved in volatile phenols synthesis and esters degradation. A specific acetate esterase activity impacting sensory profile is showed.